MENGEMBANGKAN KOGNITIF ANAK MELALUI PEMBELAJARAN DARING DI PAUD NUR MISHQI ACEH BESAR - Fittria .; Taat Kurnita Yeniningsih; Rosmiati .; Rahmatun Nessa; Rahmi . (Jurnal Ilmiah Mahasiswa Pendidikan Anak Usia Dini, 2022)
Keywords: Cognitive Development, Online Learning, Early ChildhoodThe cognitive development to in this study referred a development that needs to be developed from an early age. The research question in this study is how of process of implementing online learning to develop children's cognitive at preschool Nur Mishqi Aceh Besar. This study aims to develop the cognitive development of children aged 4-5 years through online learning during the Covid-19 pandemic. This study used the qualitative approach with a descriptive method. The research was conducted at preschool Nur Mishqi. The subjects in this study were 2 teachers and 3 parents in group A of preschool Nur Mishqi. The data collection techniques in this study were field observation and also interview. The data analysis technique was carried out in three stages, namely reducing data, presenting data, and drawing conclusions. From the results of research carried out the process of implementing online learning to implement and develop children's cognitive is the lack of cooperation between teachers and parents during learning at home to develop children's cognitive by using materials around their homes. The conclusion from this study is that in developing children's cognitive through online learning, it must be more active and there must be collaboration between teachers and parents at home so that children's cognitive development can develop according to their age, even though they are not in school during this pandemic.Abstrak: Mengembangkan kognitif yang dimaksud dalam penelitian ini adalah suatu perkembangan yang perlu dikembangkan sejak dini. Rumusan masalah dalam penelitian ini adalah bagaimana proses pelaksanaan pembelajaran daring untuk mengembangkan kognitif anak di PAUD Nur Mishqi Aceh Besar. Penelitian ini bertujuan untuk mengembangkan kognitif anak usia 4-5 tahun melalui pembelajaran daring selama pademi Covid-19. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Penelitian dilaksanakan di  PAUD Nur Mishqi. Subjek dalam penelitian ini berjumlah 5 orang yaitu 2 orang guru PAUD Nur Mishqi dan 3 orang tua kelompok A. Teknik pengumpulan data dalam penelitian ini berupa observasi lapangan dan juga wawancara dengan guru serta orang tua kelompok A. Teknik analisis data dilakukan dengan tiga tahapan yaitu mereduksi data, menyajikan data, dan menarik kesimpulan. Dari hasil penelitian yang dilaksanakan proses pelaksanaan pembelajaran daring untuk menerapkan dan  mengembangkan kognitif anak adalah  kurangnya kerjasama antara guru dan orang tua selama belajar di rumah untuk mengembangkan kognitif anak dengan menggunakan bahan-bahan yang ada di sekitar rumahnya. Kesimpulan dari penelitian ini bahwa dalam  mengembangkan kognitif anak melalui pembelajaran daring harus lebih aktif lagi serta ada kerjasama antara guru dan orang tua di rumah supaya perkembangan kognitif anak dapat berkembang sesuai usianya, walaupun tidak bersekolah semasa pandemi ini.Kata kunci: Mengembangkan  Kognitif,  Pembelajaran Daring, Anak Usia Dini